Exploring relationships between self-compassion, impostor phenomenon, and mental health among doctoral students - Clarke, Brian J.; Hartley, Michael T. (Frontiers in Psychology, 2025)
IntroductionImpostor phenomenon (IP) is widespread in doctoral education and is strongly linked to mental distress. Self-compassion is theoretically and empirically positioned as a counterbalance to the harsh self-evaluation embedded in IP, yet large-scale evidence in doctoral populations is limited.MethodsA national sample of 1,225 U.S. doctoral students completed validated measures of IP, self-compassion, anxiety, depression, and loneliness. Data were collected via online survey. Analyses included descriptive statistics, correlations, MANOVA tests comparing mental health across IP tertiles, and three hierarchical regression models testing whether self-compassion explained additional variance in distress beyond IP.ResultsIP scores were skewed high; women and non-binary students reported the highest IP. Anxiety, depression, and loneliness rose as IP increased. Across all three outcomes, self-compassion explained substantial additional variance beyond IP (ΔR² = 0.08–0.10) and meaningfully reduced IP’s standardized coefficients (47%–75%). When self-compassion was added, IP was no longer associated with loneliness, and its associations with depression and anxiety were weakened. MANOVA showed large-effect, stepwise increases in distress from low to moderate IP, while self-compassion declined at each IP level.DiscussionIP was widespread in this sample and was associated with substantially elevated levels of distress, including at low to moderate IP levels. Self-compassion demonstrated robust inverse associations with loneliness, anxiety, and depression even when IP was considered in the models. The pattern of results indicates that self-compassion is a salient correlate of mental health in the context of IP among doctoral students.